A Global Outlook on Sustainable Plant Acquisition: A Review of Scholarly Works - Sulistyowati, Tussi; Husda, Nur Elfi (PT. Riset Press International, 2023)
In today's horticultural landscape, plant acquisition is under scrutiny due to sustainability concerns and the desire to enhance the consumer experience. This study employs a qualitative literature review methodology spanning 2019 to 2023, using the Scopus database and Harzing's Publish or Perish tool to ensure article relevance and timeliness. Employing keywords like